ROLE OF PAKISTANI PRINT MEDIA IN PROMOTING CLEAN AND GREEN PAKISTAN CAMPAIGN - Iftikhar, Moneeba; Iftikhar , Urwah; Mehwish Mukhta (Journal of Arts & Social Sciences, 2020)
The aim of the research is to inspect the role of Pakistani Print Media (Daily Jang, Nawa-i-Waqt, Dawn and The News) in promoting Clean and Green Pakistan Campaign during selected time period from February to April in 2019. A sample of Total 356 newspapers was used in which 112 newspapers were taken from the month of February, 124 newspapers from the month of March and 120 newspapers from the month of April. The research was based on the Issue Attention Cycle by ‘Anthony Downs’. In this analysis, in the perspective of news and advertisements published in the selected newspapers, Chi-Square test was applied for two hypothesis testing, the test showed insignificant results for H1 and significant results for H2.Keywords: Print Media, Clean and Green Pakistan Campaign, Image Building